War Strategy Done by Gayo and Alas People Against Dutch Colonial (1901-1912) - Hairul Masri; Suprayitno Suprayitno; Ratna Ratna (Budapest International Research and Critics University, 2018)
The arrival of Dutch troops with marsose troops into the Gayo and Alas areas while attempting to crush local fighters led to wars in the area. By fomenting the spirit of war sabil, the fighters with local residents made war against the Dutch as a form of jihad against the unbelievers in order to maintain the area and belief of Islam is embraced. In the face of Dutch troops, the fighters in the Gayo and Alas region used several strategies, among which were the implantation of the Sabil War Ideology, warfare, and guerrilla warfare. Through the implementation of the strategy, the fighters are able to provide fierce resistance and can survive for a long time against the attack of Dutch troops. The Gayo and Alas people's resistance has begun to dwindle since some of the leaders of the fight have been killed and captured by Dutch troops. This led to a decline in resistance because it was no longer well organized as the combatants lost their command.